Association of intraventricular fibrinolysis with clinical outcomes in intracerebral hemorrhage: an individual participant data meta-analysis - Kuramatsu, Joji Benjamin; Gerner, Stefan T.; Ziai, Wendy; Bardutzky, Jürgen; Sembill, Jochen A.; Sprügel, Maximilian I.; Mrochen, Anne; Kölbl, Kathrin; Ram, Malathi; Avadhani, Radhika; Falcone, Guido J.; Selim, Magdy H.; et al. (Stroke, 2022)
Background: - - In patients with intracerebral hemorrhage (ICH), the presence of intraventricular hemorrhage constitutes a promising therapeutic target. Intraventricular fibrinolysis (IVF) reduces mortality, yet impact on functional disability remains unclear. Thus, we aimed to determine the influence of IVF on functional outcomes.
Collaborators: Lauren Sansing, MD, Timolaos Rizos, MD. [und viele weitere]
Gesehen am 01.12.2022